Patent ductus arteriosus with persistent pulmonary artery hypertension after transcatheter closure - Feng JQ; Kong XQ; Sheng YH; Yang R (Therapeutics and Clinical Risk Management, 2016)
Jianqi Feng,1,2 Xiangqing Kong,1 Yanhui Sheng,1 Rong Yang1 1Department of Cardiology, the First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, 2Department of Cardiology, the Second Affiliated Hospital of XuZhou Medical University, XuZhou, Jiangsu, People’s Republic of China Objectives: To observe the change in pulmonary artery systolic pressure (PASP) of patients with persistent pulmonary arterial hypertension (PAH) after patent ductus arteriosus (PDA) occlusion.Background: After occlusion of PDA in patients with PAH, some patients still tend to suffer from persistent PAH.Methods: A chest X-ray, an electrocardiogram, and an echocardiogram were performed on nine patients at 24 hours, 1 and 6 months, and 1 year serially.Results: There was a significant fall (P<0.05) in mean PASP after occlusion (to 59.3±12.7 mmHg). However, the aortic pressure and systemic arterial oxygen saturation changed slightly (P>0.05). During the follow up, there was a further fall in the PASP in five patients (No 1, 5, 6, 7, and 8). Four patients (No 2, 3, 4, and 8) showed the evidence of worsening PAH and were treated with sildenafil. Patient 2 died from acute right heart failure after a period of 11 months from the time of transcatheter closure, triggered by pulmonary infection.Conclusion: Some patients with borderline hemodynamic data with PDA and PAH can deteriorate or keep sustained PAH after PDA closure. The treatment of permanent closure to these patients must be cautious. Keywords: patent ductus arteriosus (PDA), transcatheter closure (TCC), pulmonary artery hypertension, follow-up